2019
DOI: 10.1002/adma.201901715
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Rare Earths to Magnesium and Titanium Metallurgy in Australia

Abstract: These elements have huge relevance in the modern world, in applications spanning electronics, biomedicine, structural materials, and more; many rely on their unique electronic properties as the only nonradioactive elements with electrons occupying the f-subshell. [1] However, REEs have long been topics of moderate interest for their application in metallurgy, such as the bulk purification of steels and other alloys, or the improvement of the hightemperature properties of Mg alloys. [3] In recent years, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…41 The vast majority of research on rare earth alloys focuses on lightweight magnesium (Mg) alloys, which are widely employed in high-performance automobiles and the aerospace industry. 42 Mg-based alloys are suited for application in gravity-sensitive devices due to Mg's low density of 1.7 g cm −3 , which is the lowest among typical structural metals. However, their poor ductility and susceptibility to corrosion in liquid environments restrict their widespread utilization.…”
Section: Typical Applications Eldsmentioning
confidence: 99%
“…41 The vast majority of research on rare earth alloys focuses on lightweight magnesium (Mg) alloys, which are widely employed in high-performance automobiles and the aerospace industry. 42 Mg-based alloys are suited for application in gravity-sensitive devices due to Mg's low density of 1.7 g cm −3 , which is the lowest among typical structural metals. However, their poor ductility and susceptibility to corrosion in liquid environments restrict their widespread utilization.…”
Section: Typical Applications Eldsmentioning
confidence: 99%
“…REE are used in the preparation of Mg-alloys or titanium-alloys due to their high solid-solubility, structural integrity, and corrosion resistance (by scavenging undesirable contaminants and stabilizing the oxide/hydroxide surface)an ideal property in weight-sensitive and biomedical applications (Biesiekierski et al, 2020;Willbold et al, 2015). The Pt-REE alloy has been adopted as an active and durable electrocatalyst as its negative alloying energy or enthalpy of formation confers resistance against dissolution .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the existence of an empty d orbital, the rare-earth metal could regulate the electronic band structure and lattice constant of materials to control the optical, electrical, and magnetic properties of materials. For example, Yu et al found that the 4d orbital of Y affected the dispersion bandwidth of CdO because of its antibonding expansion mechanism, the optical bandwidth of Y–CdO was increased from 2.86 to 3.27 eV, and the visible-light transmittance was greater than 80%. Torayev et al further revealed that Y distorted the lattice of BaZrO 3 and increased the atomic spacing between Y–O and Zr–O, so the proton diffusion activation energy was increased from 24.1 to 45.0 kJ/mol and inhibited the proton transport between ZrO 6 octahedrons.…”
Section: Introductionmentioning
confidence: 99%